Light scattering for thermometry of fermionic atoms in an optical lattice. - Ruostekoski, J; Foot, C; Deb, AB (2009)
We propose a method of using off-resonant light scattering to measure the temperature of fermionic atoms tightly confined in a two-dimensional optical-lattice potential. We show that fluctuations of the intensity in the far-field diffraction pattern arising from thermal correlations of the atoms can be accurately detected above the shot noise by collecting photons scattered in a forward direction, with the diffraction maxima blocked. The sensitivity of this method of thermometry is enhanced by an additional harmonic trapping potential.